2014
DOI: 10.1155/2014/398503
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antioxidant Activities of the Essential Oil from Angelica koreana Nakai

Abstract: Purpose. The purpose of this study is to determine the antifungal and antioxidant activities of the essential oil from Angelica koreana. Methods. Essential oil was obtained from the dried roots of A. koreana by steam distillation, and its composition was identified by gas chromatography and mass spectrometry (GC-MS). The minimal inhibitory concentrations (MICs) of the oil fraction and its main components were determined by broth dilution assay using common pathogenic Aspergillus and Trichophyton species. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Its composition is characterized by a 24% of sabinene, 36.7% of limonene and 12% of citronellal. The antifungal activity is probably due to sabinene, which appeared effective against A. fumigatus [ 32 ], as well as to citronellal [ 33 ]. Moreover, the present data are in full agreement with Correa-Royero et al [ 34 ], who reported effectiveness against A. fumigatus at 99.2 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Its composition is characterized by a 24% of sabinene, 36.7% of limonene and 12% of citronellal. The antifungal activity is probably due to sabinene, which appeared effective against A. fumigatus [ 32 ], as well as to citronellal [ 33 ]. Moreover, the present data are in full agreement with Correa-Royero et al [ 34 ], who reported effectiveness against A. fumigatus at 99.2 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…m -Cresol (56.12%) showed stronger DPPH scavenging activity than EO (19.31%) and sabinene (4.45%) at the concentration of 16 mg/mL. Additionally, sabinene exhibited the strongest reducing power and nitric oxide scavenging activities than the EO fraction or m -cresol [ 36 ]. Irshad et al [ 24 ] reported that A. glauca EO exhibited good DPPH radical scavenging and peroxidation inhibition activities.…”
Section: Biological Activities Of Angelica Essementioning
confidence: 99%
“…A. koreana EO and its main components, sabinene and m -cresol, showed antifungal activity against different species of Aspergillus and Trichophyton with minimal inhibitory concentrations (MICs) of 125–1000 μg/mL. In addition, EO exhibited synergistic activity when combined with itraconazole [ 36 ]. The EO of A. glauca showed appreciable antimicrobial activity against selected strains of bacteria ( Staphylococcus aureus , Bacillus subtilis , Escherichia coli, and Pasteurella multocida ) and fungi ( Candida albicans , Microsporum canis , Aspergillus flavus, and Fusarium solani ).…”
Section: Biological Activities Of Angelica Essementioning
confidence: 99%
“…Accordingly, many plants and their products, particularly essential oils, have recently been tested for their potential antioxidant activity against adverse free radicals [6,13,14,15]. Essential oils extracted from plants have become a good source of natural antioxidants [16]. Moreover, there is growing interest in the use of marine organisms as a potential source of effective antimicrobial and antioxidant compounds [17].…”
Section: Introductionmentioning
confidence: 99%